Microbiome landscape of lesions and adjacent normal mucosal areas in oral lichen planus patient - Chen, Jian; Liu, Kaikai; Sun, Xiaona; Shi, Xuanxuan; Zhao, Guanghui; Yang, Zhongjun (Frontiers in Microbiology, 2022)
The pathogenesis of oral lichen planus (OLP) remains unclear, and microbial dysbiosis has been proposed to play a role in the pathogenesis of OLP. Oral mucosal swabs from 77 OLP patients and 76 healthy subjects were collected. The bacterial community among the OLP lesion, the adjacent normal mucosal, and the oral mucosal surface in healthy people were analyzed by 16S sequencing. The factor of gender and age that may affect the flora distribution of OLP patients were explored. Results indicate no significant difference in microbiota between OLP and the adjacent group. Compared with the healthy group, Neisseria, Haemophilus, Fusobacterium, Porphyromonas, Rothia, Actinomyces, and Capnocytophaga significantly increased in the OLP group. Actinomyces increased in male OLP patients, and the other six bacteria increased in female OLP patients. In female OLP patients, Lautropia and Dialister were positively correlated with age. While in male OLP patients, Moraxella, Porphyromonas, and Fusobacterium were positively correlated with age. Functional enrichment analysis suggested that abnormal energy metabolism related to ATP synthases, abnormal transport and metabolism of glycans, amino acids, and vitamins, and disorders of the local immune microenvironment might exist in OLP lesion.